Cinética de expressão e localização de indutor de metaloproteínases (EMMPRIN) durante o desenvolvimento de lesão periapical induzida em camundongos - Sousa, Natalia Guimarães Kalatzis [UNESP] (2013)
This study evaluated the kinetics of expression and location of EMMPRIN and the correlation of its expression with expression of MMPs -1, -2 and -9 and with alveolar bone loss during the development of experimentally induced periapical lesions in mice. A total of 40 C57BL/6 wild-type mice (WT) were used. The periapical lesions were induced in first lower molars. After 7, 14, 21 and 42 days, the animals were killed and the mandibles were removed. Mice without pulp exposure served as controls. Measurement of periapical lesions was performed in micro-computed tomography. mRNA levels of EMMPRIN, MMPs-1, -2, and -9 were detected by real time RT-PCR. Presence, localization, and expression of EMMPRIN and MMPs were evaluated by immunohistochemistry. Data were analyzed using ANOVA, Bonferroni and Spearman correlation tests with significance level of 5%. The results showed that periapical lesion area was significantly increased from 7 to 14 days (83%) and thereafter become stable. In the control group, EMMPRIN was strongly expressed in odontoblastic layer of the dental pulp. At 7, 14, 21 and 42 days there was intense immunostaining for EMMPRIN, MMPs -1, -2 and -9 in the adjacent region of apical foramen, where there was dense inflammatory infiltrate. These proteins were expressed in other parts of the periapical lesion occasionally. EMMPRIN, MMP-1, -2 and -9 were intensely expressed in mononuclear and polymorphonuclear inflammatory cells and discretely expressed in fibroblasts. In the periapical region, the EMMPRIN immunostaining was higher at 7, 14, 21 and 42 days compared with control. The expression of EMMPRIN gene was higher in control group compared with 7, 14, 21 and 42 days. The expression of MMP-1 gene increased at 7 days and stays elevated until 42 days. The mRNA levels of MMP -2 and -9 increased significantly at 14 days and returned to control level at 21 and 42 days. The EMMPRIN immunostaining was...